2012
DOI: 10.3126/kumj.v9i1.6262
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Invasive Pneumococcal Disease in Patan Hospital, Nepal

Abstract: Background Pneumococcal infection is one of the leading causes of pneumonia, meningitis and septicemia in developing countries. It accounts for one million deaths each year in children. Objectives The objective of this study is to see the clinical profile of invasive pneumococcal disease, antibiotics sensitivity pattern and prevalent serotypes in children admitted at Patan Hospital. Methods This is a retrospective analytical study conducted in the department of Paediatrics, Patan hospital. The lab data of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Other Nepalese studies have also demonstrated the effectiveness of penicillin in pneumococcal infections. 6,7 The National Committee on Immunization Practice (NCIP) of Nepal recommends three doses of PCV 10 vaccine containing serotypes 1, 4, 5, 6B, 7F, 9V, 14, 18C, 19F, and 23F, at 6 and 10 weeks and then at 9 months, based on prevalence and serologic test results. 12 A 2014 systematic review supported the three-dose schedules recommended by the WHO and found it to be effective in reducing clinical as well as radiologically confirmed pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other Nepalese studies have also demonstrated the effectiveness of penicillin in pneumococcal infections. 6,7 The National Committee on Immunization Practice (NCIP) of Nepal recommends three doses of PCV 10 vaccine containing serotypes 1, 4, 5, 6B, 7F, 9V, 14, 18C, 19F, and 23F, at 6 and 10 weeks and then at 9 months, based on prevalence and serologic test results. 12 A 2014 systematic review supported the three-dose schedules recommended by the WHO and found it to be effective in reducing clinical as well as radiologically confirmed pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The few previous studies of pneumonia in Nepal have focused on description of the antibiotic sensitivity patterns and serotypes of pneumococci in tertiary care centers within the capital city. [5][6][7] Research on community-acquired pneumonia (CAP) in other regions of the country is lacking. Pneumococcal conjugate vaccination (PCV) has demonstrated efficacy against various serotypes of Streptococcus pneumoniae and is now part of routine immunization schedule in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…In Nepal, pneumonia accounted for 10% of all childhood acute respiratory infections (ARI) in 2017 with an annual incidence of 66 cases per 1000 under-five children [ 4 ]. Previous studies from tertiary care settings in Nepal show that most of the pneumonia in under-five children were viral in origin and those with bacterial etiology were sensitive to the penicillin group of antibiotics [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Long-term surveillance of invasive pneumococcal disease (IPD) at Patan Hospital, Nepal has shown pneumococcal serotypes 1, 5 and 14 to be the cause of the majority of IPD. 6 All of these serotypes are covered by available PCVs. 7,8 The incidence of childhood pneumococcal pneumonia is high up to the age of 5 years.…”
Section: Introductionmentioning
confidence: 99%